PEMBUATAN DAN KARAKTERISASI KARBON AKTIF DARI BAMBU BETUNG DENGAN AKTIVASI MENGGUNAKAN ACTIVATING AGENT H2O - Rijali, Anggiyan; Malik, Usman; ', Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Research on syinthesis of activated carbon has been conducted from bamboo betung with carbonization temperature of 400°C, 500°C and 600°C with duration time of 20, 40 and 60 minutes, respectively. Physical activation was carried out at 900°C for 20, 40, and 60 minutes with H2O steam as an activating agent. Bamboo betung characteristics as activated carbon was studied by analyzing shrinkage mass levels, proximate test, activated carbon absorption of the iodine and yield. Increasing of mass shrinkage was proportional to carbonization time. the higher carbonization temperature, the smaller water content and the greater content of ash. The higher temperature time resulted the higher value of iodine, and the longer activation time could decreased the yield. The best results of activated carbon was obtained at a temperature of 600°C in 60 minutes with shrinkage levels of mass of 69%, 3.8% of moisture content, 8.1% of ash contents and 31.5% of yield. Whereas the iodin number was found to be 379 mg/g.